1995
DOI: 10.3719/weed.39.243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seeding Date on Flowering and Seed Production of Velvetleaf (Abutilon theophrasti Medic.)

Abstract: In 1993 a field experiment was conducted to determine the influence of seeding date on flowering and seed production of velvetleaf at Kyushu National Agricultural Experiment Station, Nishigoshi, Kumamoto, on thick high humic Andosols (Melanudands). Velvetleaf seeds were seeded monthly from April to November in plots fertilized in advance at 1kg N, 1kg P2O5 and 1kg K2O/a with a compound fertilizer. Flowering and seed production of the emerged plants were evaluated. Flowering was observed in the April to August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…These results suggest that seeds with a strong weedy nature entered Japan, where they were transferred to dairy farms all over, and mixed with the 23 millions (t/year) of imported grains. Their biological characteristics, such as days to flowering, seed dormancy, fecundity, and plant height at the first flowering, correspond to those of the present invasive velvetleaf in Japan reported previously (Sato et al 1994).…”
Section: Characteristics Of Newly Introduced Accessions and The Possisupporting
confidence: 85%
See 1 more Smart Citation
“…These results suggest that seeds with a strong weedy nature entered Japan, where they were transferred to dairy farms all over, and mixed with the 23 millions (t/year) of imported grains. Their biological characteristics, such as days to flowering, seed dormancy, fecundity, and plant height at the first flowering, correspond to those of the present invasive velvetleaf in Japan reported previously (Sato et al 1994).…”
Section: Characteristics Of Newly Introduced Accessions and The Possisupporting
confidence: 85%
“…Among the germplasms preserved in the National Plant Germplasm System (NPGS) in the USA, we found many velvetleaf accessions. By comparing their reproductive characteristics with those of the Kashima accessions, we can evaluate the relative characteristics of the Kashima accessions and refer to previous reports about the growth habits of the present invasive velvetleaf (Tateno & Kobayashi 1993;Sato et al . 1994;Sato et al .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, velvetleaf emerging at the first emergence date produced 21,000 seeds m Ϫ2 compared with 11,800 and 5,300 seeds m Ϫ2 for the second and third emergence date, respectively, in 2003 (P Ͻ 0.05). Sato et al (1994) also reported decreasing seed production for velvetleaf grown in monoculture with later velvetleaf emergence dates (Table 3).…”
Section: Velvetleaf Seed Production In Monoculture (Final Harvest)mentioning
confidence: 99%
“…In this species, flowering and seed production showed a short-day photoperiodic response (Sato et al 1994), and its competitive ability could be influenced by the daylength. However, Steinmaus and Norris (2002) indicated that velvetleaf had a range of growth responses to a variety of light availabilities and that it should have little difficulties in becoming fully established in the irrigated agroecosystems of Mediterranean-type regions.…”
Section: Resultsmentioning
confidence: 99%
“…Big differences in the percentage of germinability of seeds from the A1 and A2 cohorts were found (81% and 37%, respectively). These results are in concordance with those of Sato et al (1994), who noted that seeds of this species produced by earlier germinated plants were heavier and more vigorous than those which germinated later. Two causes can explain these differences: (1) a higher dormancy appears in the seeds produced by late germinated plants or (2) incomplete fruit and seed ripening in the plants occurs in these later cohorts.…”
Section: Seed Germinabilitymentioning
confidence: 99%